(untitled) (Economic studies journal, 2025)
This study aimed to measure the impact of oil prices shock on the Kaldor’s magic square variables in the Libyan economy during the period (1980-2020) using the vector autoregressive methodology (VAR) . The results of the unit root test (ADF) and (PP) indicated that the time series are non stationary at the level، while they stationary at first difference. Also The study concluded that there is no long-run equilibrium relationship between variables. The results of Granger-Causality also found that there is a single causal relationship that goes from oil prices to Gross Domestic Product ، Trade balance inflation ، Unemployment. The impulse response functions showed that the oil prices shock had varying effects on the Kaldor’s magic square variables in the Libyan economy in the long run، as the effect was negative on the domestic product، trade balance، and unemployment، while the effect of the shock was positive on the inflation variable.On the other hand، the response of the variables to the oil prices shock in the short run was Zero for the GDP and Inflation variable، positive for the trade balance variable، and had a negative effect for the unemployment variable